2004
DOI: 10.1073/pnas.0400303101
|View full text |Cite
|
Sign up to set email alerts
|

Complex molecular architecture of beet yellows virus particles

Abstract: Closteroviruses possess exceptionally long filamentous virus particles that mediate protection and active transport of the genomic RNA within infected plants. These virions are composed of a long ''body'' and short ''tail'' whose principal components are the major and minor capsid proteins, respectively. Here we use biochemical, genetic, and ultrastructural analyses to dissect the molecular composition and architecture of particles of beet yellows virus, a closterovirus. We demonstrate that the virion tails en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
74
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 45 publications
0
74
0
1
Order By: Relevance
“…The TGB MPs are involved in multiple interactions between themselves (18,38), while tubule-forming MPs enclose virions into the tubes formed during infection (29). In addition to accumulation in PDs, BYV Hsp70h is incorporated to virion tails that function in virus transport (2,36,42,47,53).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TGB MPs are involved in multiple interactions between themselves (18,38), while tubule-forming MPs enclose virions into the tubes formed during infection (29). In addition to accumulation in PDs, BYV Hsp70h is incorporated to virion tails that function in virus transport (2,36,42,47,53).…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, each of these four proteins is an integral component of the ϳ1,400-nm-long filamentous virions with CP coating ϳ97% of the 15.5 kb RNA genome. The remaining three proteins, CPm, p64, and Hsp70h, assemble a ϳ100-nm-long tail that encapsidates a 5Ј-terminal, ϳ600-nucleotide (nt)-long RNA segment (47). An additional, 20-kDa, tail protein is not required for the cell-to-cell movement, but is essential for the viral transport through the phloem (53).…”
mentioning
confidence: 99%
“…Although the other three recombinant capsid components do not bind specifically to the whitefly vector, we cannot rule out the possibility that, in the context of the assembled virion, they may have some yet unknown functions associated with virus transmission. Because the CPm, CP, HSP70h, and P59 are interacting capsid components (11,33,34), it is intriguing that in the absence of a complete CPm, the agropR6-5b mutant is still capable of systemic plant infection and encapsidation, perhaps by one or more of the other three components compensating for the truncated CPm (10). However, it is clear from our data that virion retention and transmission by vectors are dependent on the presence of a complete CPm and cannot be substituted or compensated for.…”
Section: Discussionmentioning
confidence: 99%
“…The latter is dispensable for virion formation and virus cell-to-cell movement, but is essential for the viral systemic transport through the plant vascular system (Prokhnevsky et al, 2002). Atomic force microscopy studies demonstrate that the closterovirus virion terminal structure has a complex morphology and consists of three distinct segments, of which the tip segment is likely to be formed by the p20 protein (Peremyslov et al, 2004). Since the CPm, Hsp70h and p64 proteins are required for BYV cell-to-cell movement (Alzhanova et al, 2000;Peremyslov et al, 1999;Prokhnevsky et al, 2002), it has been concluded that the terminal structure represents the specialized device evolved to facilitate translocation of closterovirus virions to and through plasmodesmata .…”
Section: Role Of Virions In Cell-to-cell Transport Of Filamentous Virmentioning
confidence: 99%
“…The main virion part (approximately 95 % of its length) is made of the CP, while the remaining segment, which is located at the virion end encapsidating the 5¢-terminal region of genomic RNA, is formed by the CPm (Agranovsky et al, 1995;Peremyslov et al, 2004;Satyanarayana et al, 2004). Additionally, the CPm-formed region of BYV virions contains three other viral proteins, namely an Hsp70 homologue (Hsp70h), a p64 protein with a CP-like structural domain in its C-terminal region and p20 (Kiss et al, 2013;Napuli et al, 2000Napuli et al, , 2003Tian et al, 1999).…”
Section: Role Of Virions In Cell-to-cell Transport Of Filamentous Virmentioning
confidence: 99%